Pemicu Audit Delay pada Perusahaan Go Public di Indonesia Berbasis Laporan Keuangan (Tahun 2008-2012) - Setiawan, Andik; Handayani, Dwi; Mujilan, Agustinus (JRMA | Jurnal Riset Manajemen dan Akuntansi, 2014)
The financial statement is an important instrument for companies. Audit delay is an important factor that can influence it. The time difference between closing dates to the date of issuance of the company independent auditors report known as the audit delay. The purpose of this research is to examine the effect of firm size, company that announced loss, profitability, industrial sector, auditor opinion, and the public accountant firm size toward the audit delay. The population in this research is the manufacturing companies and non manufacturing companies which is listed on the Indonesian Stock Exchange in periode 2008-2012. This research used 270 samples of companies chosen by purposive sampling technique. Data sources obtained from the Indonesia stock exchange. Data analysis is performed by multiple linier regresion by statistical software SPSS. The result showed that the auditor opinion has significant positive effect, firm size and company that announced loss has significant negative effect on audit delay. While the profitability, industrial sector and public accountant firm size has no significant effect on audit delay.